1988
DOI: 10.1037/0012-1649.24.5.690
|View full text |Cite
|
Sign up to set email alerts
|

Verbal interaction in families of normal and expressive-language-delayed children.

Abstract: Developmental expressive language disorder (ELD) is a condition characterized by a delay in the development of expressive language compared with receptive language and IQ. Conditions that might contribute to the origins or maintenance of ELD are poorly understood. Unusual verbal interactions between parents and ELD children might be implicated in the origins of ELD or might represent parental reactivity to the child's limited expressive skills. We compared verbal interactions in the homes of 28-month-old ELD c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
3
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 37 publications
5
40
3
1
Order By: Relevance
“…Read Together, Talk Together is a dialogic reading kit that was designed on the research conducted by Whitehurst and colleagues Whitehurst et al, 1988). It includes colorfully illustrated children's books appropriate for the age level of 4 or 5 years.…”
Section: Dialogic Reading Intervention Booksmentioning
confidence: 99%
See 2 more Smart Citations
“…Read Together, Talk Together is a dialogic reading kit that was designed on the research conducted by Whitehurst and colleagues Whitehurst et al, 1988). It includes colorfully illustrated children's books appropriate for the age level of 4 or 5 years.…”
Section: Dialogic Reading Intervention Booksmentioning
confidence: 99%
“…That study, however, did not assess the quality of the parent-child interactions during shared reading. Investigation of the natural reading behaviors of parents with their preschoolers found that parents do not typically engage in interactive reading with their children (Whitehurst et al, 1988). In fact, parents' reading styles typically include few dialogues, and these dialogues involve mainly yes/no questions or directives.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In some studies, interventions consisted in training sessions repeated frequently over a relatively long period of time (Lever & Sénéchal, 2011;Peterson, Jesso & McCabe, 1999;Whitehurst et al, 1988), while in others the intervention involved one short session in which children were questioned about the causes of the story events and/or the internal state of the characters (Eaton, Collis, & Lewis, 1999;Shiro, 2003;Silva, Strasser & Cain, 2014;Veneziano & Hudelot, 2006Veneziano, 2016). In some studies, the narratives obtained were conversationally co-constructed between the child and the experimenter (e.g.…”
Section: What Is Known About This Ability?mentioning
confidence: 99%
“…Few studies have examined mothers and late-talking children in the 2-to 3-year age range, and only one such study has limited the sample to children who are receptively normal (Whitehurst et al, 1988). In that study, data were collected during the family dinner hour, and only the communicative behavior of the parents was examined in any depth.…”
mentioning
confidence: 99%